Work-life conflict and job mobility intentions - Joseph, Damien (2013)
This study takes the first step in IT literature to examine the role of time-based and strain-based work-life conflicts on turnover and turnaway. Prior research on work-life (and work-family) conflicts and turnover typically examines it as a unidimensional construct. This study examines work-life conflict as a multidimensional construct comprising of time-based and strain-based conflicts. In this study, time and strain (i.e. demands on energy) are conceptualized as resources. The Conservation of Resources Theory is utilized to develop two sets of hypotheses relating time and strain to turnover and turnaway intentions. The hypotheses are tested on a sample of IT professionals drawn from a local IT professional association. The results indicate that time-based conflicts are not related to turnover and turnaway intentions. Strain-based conflicts, however, are positively related to turnover and turnaway intentions. This study concludes with a discussion of this pattern of results and presents subsequent research directions, which the authors are pursing.